1993
DOI: 10.1111/j.1365-2230.1993.tb00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of fluconazole in serum, stratum corneum, epidermis-dermis (without stratum corneum) and eccrine sweat

Abstract: The distribution in the skin of orally active antifungals and other drugs claimed to be active in the treatment of skin diseases is of major importance, but to date has been studied only rarely. In the present study the distribution of fluconazole in stratum corneum, epidermis-dermis (without stratum corneum), eccrine sweat and serum was studied in human male volunteers after dosages of 50 mg daily for 12 days and 150 mg once weekly for 2 weeks. In the present study high levels of fluconazole were found especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 8 publications
4
96
0
3
Order By: Relevance
“…Fluconazole concentrations within the dermis are similar to those in plasma (216,217), but concentrations in the stratum corneum are up to 40 times those in plasma (217,218) (Fig. 7).…”
Section: Skin and Nailsmentioning
confidence: 78%
See 1 more Smart Citation
“…Fluconazole concentrations within the dermis are similar to those in plasma (216,217), but concentrations in the stratum corneum are up to 40 times those in plasma (217,218) (Fig. 7).…”
Section: Skin and Nailsmentioning
confidence: 78%
“…7). The clearance of fluconazole from the stratum corneum is also significantly slower than that from the plasma and other skin layers, with concentrations that decline 2 to 3 times more slowly than the plasma concentrations (215,217,218). Interestingly, once-weekly oral dosing of 150 mg for 2 weeks results in higher fluconazole concentrations in the stratum corneum relative to those in the epidermis/dermis, sweat, and serum than those obtained by daily dosing at 50 mg for 12 days (217).…”
Section: Skin and Nailsmentioning
confidence: 94%
“…This drug is a lipophilic allylamine compound. terbinafine penetrates keratinized tissues, and enters the stratum corneum and sebum by direct diffusion through the dermis and living epidermis (Faergemann 1997, Faergemann et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…31 Thus, ACP1-GM1 with particle size of 233.0 nm should have the ability to form an occlusive film on the surface of skin, increase the hydration of SC, and improve the permeation of terbinafine into skin. This indicated that the application of ACP1-GM1 for 12 …”
Section: In Vitro Transdermal Penetrationmentioning
confidence: 99%
“…7,8 Moreover, the TB treatment duration is shorter in most cases. 9,10 Based on several clinical studies conducted in humans [11][12][13] and animals, 14,15 it was noted that TB accumulates in the skin and persists at high concentrations for up to several weeks after discontinuing drug application. The superior efficacy of TB after the end of the treatment period is attributed to its fungicidal effect in addition to the favorable pharmacokinetic characteristics of substantial and rapid penetration into the stratum corneum (SC), where it remains in the skin for a long time after discontinuing treatment.…”
Section: Introductionmentioning
confidence: 99%